Hermeneutic Method In Understanding Hadith - Lukman Affandi*; Lilik Andaryuni; Ashar Pagala (Universitas Syiah Kuala, 2023)
Hadith, like the Qoran, is a text that comes from the past and is intended as a reference for Muslims in the past, present, and future. In understanding the products of the past, there are many ways to use their understanding for the benefit of the people. Hermeneutics exists as a new way to understand past product texts. Similar understanding in the process of understanding the Koran has taken clear steps to understand Hadith using the hermeneutic method. Hermeneutics as an alternative method of interpretation is new in the Islamic world, but that does not mean it did not exist before it was applied in a narrow or broad sense. In general, hermeneutics in religious texts, especially the Koran and Hadith, aims to find the original meaning of the text by placing the text in a social-historical environment. With the hermeneutic method, it is also considered as a representative of reformers, who have contributed a lot to the development of Islam, so that religious texts can be more harmonious according to the times without losing their authenticity.